Segmentación de la red y priorización del ancho de banda para mejorar el rendimiento y seguridad la UNIVERSIDAD NACIONAL DE SAN MARTÍN – TARAPOTO - Ramírez Rodríguez, Mirko (2015)
This research aims to make the network segmentation and prioritization of bandwidth use, because the current design of the network of the University City of the National University of San Martin - Tarapoto is a flat network with VLAN default, therefore there is no adequate segmentation collision domain and broadcast domain, which drastically affects the performance of the same level of packet transmission between buildings that are ends of the star and the hub node. This causes network latency on dates and times peak transfer rate degraded by excessive traffic and not segmented data and damaging or retarding the academic and administrative processes. Therefore, as part of the solution to the needs identified in this research, redesigning the network to support Virtual LAN networks arises, and thus target areas subnets for a higher level of protection; provide security Control Lists (ACL's access, security of emerging technologies in Windows). Following the segmentation of the network, prioritizing bandwidth according to VLAN segments created is done, identifying which buildings require a higher bandwidth adequately discriminate access according to its priority, allowing it to improve consumption bandwidth (QoS), implementing protocols to disapprove the network management, enabling lower costs and raise productivity UNSM-T.